Personal Saving Behavior and the Rate of Inflation - Howard, David H. (The Review of Economics and Statistics, 1978)
PERSONAL saving rates, i.e., the ratios of personal saving to personal disposable income, in many industrialized countries have risen dramatically in recent years. A number of attempts to explain the phenomenon of rising saving rates coinciding with price inflation have drawn upon the work of George Katona (1975), who has stressed the feeling of uncertainty and pessimism about the future caused by inflation that, in turn, encourages saving. In this paper a general model of aggregate household saving behavior is formulated. Data on Canada, Germany, Japan, the United Kingdom, and the United States are used to estimate the personal saving function in each of the countries and the results are used to test various hypotheses about personal saving behavior. This paper has two major objectives: to test for a direct influence of inflation on personal saving after taking into account the influence of other relevant factors, including any indirect channels by which inflation may exert an influence (e.g., the level of real liquid assets); and to determine what factors in each country are important for explaining saving behavior.